2015
DOI: 10.1261/rna.049197.114
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel eukaryal nick-sealing RNA ligase from Naegleria gruberi

Abstract: The proteome of the amoebo-flagellate protozoan Naegleria gruberi is rich in candidate RNA repair enzymes, including 15 putative RNA ligases, one of which, NgrRnl, is a eukaryal homolog of Deinococcus radiodurans RNA ligase, DraRnl. Here we report that purified recombinant NgrRnl seals nicked 3 ′ -OH/5 ′ -PO 4 duplexes in which the 3 ′ -OH strand is RNA. It does so via the "classic" ligase pathway, entailing reaction with ATP to form a covalent NgrRnl-AMP intermediate, transfer of AMP to the nick 5 ′ -PO 4 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Electron density showed that AMP is covalently linked to the motif I Lys170 side-chain in the active site of the NTase domain (Fig. S2), consistent with our biochemical evidence that at least half of the recombinant NgrRnl protein was NgrRnl-AMP (29). The adenosine nucleotide is in the syn conformation.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Electron density showed that AMP is covalently linked to the motif I Lys170 side-chain in the active site of the NTase domain (Fig. S2), consistent with our biochemical evidence that at least half of the recombinant NgrRnl protein was NgrRnl-AMP (29). The adenosine nucleotide is in the syn conformation.…”
Section: Resultssupporting
confidence: 85%
“…The structure highlights direct contacts to the ATP γ-phosphate from the N domain of NgrRnl, via Arg4 and Lys121, and to the second Mn 2+ coordination complex via Asp53. The N domain contacts to ATP and Mn2 in the Michaelis complex aid in orienting the PP i leaving group during step 1 lysine adenylylation, and account for the severe decrement in step 1 activity when the N domain is deleted (29). ) 2 Michaelis complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations